2015
DOI: 10.1016/j.radonc.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Rectal bleeding after radiation therapy for endometrial cancer

Abstract: Background & Purpose The goals of this study were to determine the rate and risk factors of rectal bleeding (RB) after external beam radiotherapy and vaginal brachytherapy (EBRT+VB), and to compare this data to previously unreported RB rates from PORTEC-2 patients receiving EBRT or VB alone. Materials & Methods Retrospective chart review identified 212 endometrial cancer patients receiving adjuvant EBRT+VB between 2006–2013. Patient-reported RB data were also obtained from PORTEC-2 patients randomized to EBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, this early decrease might be explained by a hidden treatment effect of pelvic radiotherapy on microscopic or early rectal cancer. In contrast, the late effect of radiotherapy might increase the risk of secondary cancer, consistent with both the present findings and our previous findings (Mitra et al 2015 ). This further supports the need for rectal cancer surveillance among long-term survivors of EC who have undergone pelvic radiotherapy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this early decrease might be explained by a hidden treatment effect of pelvic radiotherapy on microscopic or early rectal cancer. In contrast, the late effect of radiotherapy might increase the risk of secondary cancer, consistent with both the present findings and our previous findings (Mitra et al 2015 ). This further supports the need for rectal cancer surveillance among long-term survivors of EC who have undergone pelvic radiotherapy.…”
Section: Discussionsupporting
confidence: 94%
“…The increased risk of rectal cancer might be explained by late sequelae of pelvic radiotherapy given to treat primary EC. Rectal bleeding due to rectitis occurs in approximately 18% of women who receive pelvic radiotherapy for EC; it is also a manifestation of the late sequelae of pelvic radiotherapy (Mitra et al 2015 ). The risk of rectal cancer was higher (SIR, 1.90, 95% CI 1.74–2.09) among 104,760 cancer survivors (from 13 institutions in 5 countries with more than 40 years of follow-up) who received pelvic radiotherapy, than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Vance et al (23) reported relatively better 2- and 5-year disease-specific (90%, 77%) and overall survival (84%, 72%) rates among women with early-stage EC (87% FIGO stage I and 13% FIGO stage II disease). Fokdal et al (38) showed 2-year LC of 92%, with disease-free survival and overall survival rates of 59% and 78% respectively. In contrast, Jhingran et al (1) showed lower 2-year LC (82%) and OS (69%) rates, when compared to our MR-based ISBT subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal bleeding is most related to the use of external beam RT (38). Three-year actuarial local control, progression-free, and overall survival rates were 100%, 88%, and 87%, respectively, for patients who received MR-guided ISBT; and 78%, 62%, 84%, respectively, for patients who had CT-based treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation proctitis is an inflammation of the distal rectum, which occurs in patients treated for genitourinary or gynaecological malignancies. Symptoms include bloody diarrhoea and cramps that can develop within weeks to years after initiation of radiotherapy of the pelvic region (Mitra et al., 2015).…”
Section: Causes Of Rectal Bleedingmentioning
confidence: 99%